UMP Co-Curriculum Centre to be branded under new name - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 22 February 2021 - The Universiti Malaysia Pahang (UMP) Co-Curriculum Centre building located at UMP Pekan is now complete and is to be branded with a new name in line with its role in the future.